2019
DOI: 10.1186/s40644-019-0274-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biparametric and multiparametric MRI in the diagnosis of prostate cancer

Abstract: PurposeTo compare the diagnostic accuracy of biparametric MRI (bpMRI) and multiparametric MRI (mpMRI) for prostate cancer (PCa) and clinically significant prostate cancer (csPCa) and to explore the application value of dynamic contrast-enhanced (DCE) MRI in prostate imaging.Methods and materialsThis study retrospectively enrolled 235 patients with suspected PCa in our hospital from January 2016 to December 2017, and all lesions were histopathologically confirmed. The lesions were scored according to the Prosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 58 publications
(56 citation statements)
references
References 33 publications
(33 reference statements)
1
46
0
Order By: Relevance
“…7,8 Additionally, DCE-MRI with gadolinium chelate increases the burdens on the patient in terms of potential for gadolinium retention and nephrogenic systemic fibrosis, examination time, and cost. [9][10][11][12][13][14] Therefore, interest is growing in performing abbreviated prostate MRI protocols without DCE-MRI, as a procedure termed "biparametric MRI" (bpMRI). 8 A number of studies on bpMRI using PI-RADS v2 have reported that the diagnostic accuracy of bpMRI for detecting csPC is comparable to that of mpMRI.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7,8 Additionally, DCE-MRI with gadolinium chelate increases the burdens on the patient in terms of potential for gadolinium retention and nephrogenic systemic fibrosis, examination time, and cost. [9][10][11][12][13][14] Therefore, interest is growing in performing abbreviated prostate MRI protocols without DCE-MRI, as a procedure termed "biparametric MRI" (bpMRI). 8 A number of studies on bpMRI using PI-RADS v2 have reported that the diagnostic accuracy of bpMRI for detecting csPC is comparable to that of mpMRI.…”
mentioning
confidence: 99%
“…8 A number of studies on bpMRI using PI-RADS v2 have reported that the diagnostic accuracy of bpMRI for detecting csPC is comparable to that of mpMRI. [10][11][12][13][14][15] Han et al 16 compared the diagnostic performance between bpMRI and mpMRI using PI-RADS v2.1; however, the pathologic results in that study were obtained by systematic transrectal ultrasonography (TRUS)-guided biopsy or systematic TRUSguided biopsy plus TRUS-guided cognitive-targeted biopsy. A recent multicenter, randomized, noninferiority trial has shown that in men with a clinical suspicion of PC, the detection ability of csPC was significantly higher in MRI-US fusion-guided prostate-targeted biopsy (MRGB) than in standard systematic TRUS-guided biopsy.…”
mentioning
confidence: 99%
“…13,14 Interestingly, biparametric MRI (bp-MRI), consisting of T2-weighted imaging and diffusion-weighted imaging without dynamic contrastenhanced imaging, has shown comparable efficacy in detecting clinically significant PCa by mp-MRI. 13,15 It could be speculated that bp-MRI may also have potential value in predicting adverse pathological features in PCa patients.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, there has been investigation of the efficacy of abbreviated noncontrast MRI examinations in the detection and risk stratification of PCa. Biparametric MRI (bpMRI), which only employs anatomical (T 2 ‐weighted) and diffusion‐weighted sequences, is showing great promise …”
mentioning
confidence: 99%
“…One study applied the IMPROD bpMRI protocol to 364 men with csPCa (defined as Gleason score ≥3 + 4). All patients received systematic biopsies, but high Likert scores initiated additional cognitively guided MRI targeted biopsies. Their method achieved an accuracy of 70% and negative predictive value of 95% in detecting csPCa.…”
mentioning
confidence: 99%